Assessing the Skillset Impacting the Readiness of HVAC Bachelor's Final Year Students for Industrial Revolution 4.0 (IR 4.0) - Razali, Nizamuddin; Alex Moriom, Marlini; Baharudin, Nurhayati; Masran, Saiful Hadi; Md Nor, Mohd Hairwan; Zahmani, Qamar Fairuz (Online Journal for TVET Practitioners, 2024)
The Industrial Revolution 4.0 (IR 4.0) represents a transformative phase in industrial development, characterized by advanced technologies such as the Internet of Things (IoT) and Cyber Physical Systems (CPS). This shift poses significant challenges and opportunities for industries, including Heating, Ventilation, and Air Conditioning (HVAC). Addressing the readiness of HVAC students for IR 4.0, this study investigates the gap in skills and competencies required in this new era. It specifically examines the preparedness of final year bachelor’s degree students in HVAC, focusing on the balance between technical and non-technical skills. Employing a qualitative descriptive research design, the study involved a sample of 100 final year HVAC students from Universiti Tun Hussein Onn Malaysia (UTHM) and Universiti Teknikal Malaysia Melaka (UTeM). A structured questionnaire, developed based on a thorough literature review and validated through expert reviews and a pilot study, was used to collect data. The questionnaire assessed students' self-evaluation of their readiness, understanding of technical skills, and development of non-technical skills relevant to IR 4.0. The analysis revealed that students possess a high level of perceived readiness for IR 4.0, with non-technical skills emerging as significant contributors to their preparedness. These skills accounted for 44% of the variance in students' readiness. The findings underscore the importance of integrating non-technical skills into the HVAC curriculum, highlighting their role in equipping students to navigate the evolving technological landscape of IR 4.0. In conclusion, the study provides comprehensive insights into the skillsets necessary for HVAC students to thrive in the IR 4.0 era. It emphasizes the need for educational institutions to adapt their curricula and pedagogical strategies to include a balanced focus on both technical and non-technical skills, thereby enhancing student employability and readiness for the challenges of the modern industrial world.